Influenza vaccination for older adults - Talbot, H. Keipp B.; Libster, Romina; Edwards, Kathryn (Human vaccines & immunotherapeutics, 2012)
Influenza vaccines were developed in the 1930s and were shown in randomized clinical trials to prevent influenza in young healthy adults. The significant morbidity and mortality associated with influenza in adults, age 65 y and older, prompted the early recommendation for influenza vaccination in that age group, based on efficacy data in younger adults. Subsequently a number of studies have demonstrated vaccine effectiveness in older adults, but it appears to be lower than in younger adults. New vaccines are being developed with enhanced immunogenicity to improve the protection of older adults. In the meantime, the currently licensed influenza vaccines need to be administered annually to prevent the estimated 90,000 hospitalizations and 5,000 deaths attributed to influenza in adults ≥65 y of age each year.